2018
DOI: 10.1055/a-0597-8877
|View full text |Cite
|
Sign up to set email alerts
|

Giant Prolactinomas: Outcomes of Multimodal Treatments for 42 Cases with Long-Term Follow-Up

Abstract: Giant prolactinomas represent a rare entity of pituitary tumors so that the management of these patients is still a prevalent challenge at present. Paying special attention to the treatment strategy and outcomes, we presented a large series of 42 cases looking forward to share our understanding and experience in management of these patients. Male patients accounted for 71.4% of this series and were relatively younger (35.70±2.42 vs. 52.00±3.55 years, p=0.0011) and harbored bigger tumors (14.57 vs. 7.74 cm, p=0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Giant prolactinoma can present with very high PRL level [ 6 , 7 , 9 ]. However, no consistent correlation has been reported between PRL level and tumor size [ 5 , 6 , 9 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Giant prolactinoma can present with very high PRL level [ 6 , 7 , 9 ]. However, no consistent correlation has been reported between PRL level and tumor size [ 5 , 6 , 9 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Giant prolactinoma can present with very high PRL level [ 6 , 7 , 9 ]. However, no consistent correlation has been reported between PRL level and tumor size [ 5 , 6 , 9 , 11 , 12 ]. Dopamine agonists, including bromocriptine and CAB, are effective first-line therapy and generally well tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that DA affects the pituitary D2 receptors that inhibit the activity of adenylyl cyclase and, as a result, suppress gene transcription and prolactin secretion. However, DAs have a significant effect on other dopamine, serotonin androgenic receptors, which leads to severe neurological disorders such as postural hypotension or dyskinesia, psychosis, or mania, which provoke compulsive states [25][26][27]. Patients with pituitary microadenomas were offered for medication therapy for several years with a possible biochemical remission of 40-100 % [17], or EET surgery over the micro and macroprolactinomas (tumor should be removed in capsule).…”
Section: Discussionmentioning
confidence: 99%
“…The eligibility criteria consisted of the following items: (1) only studies that included patients who had been diagnosed with prolactinoma. Prolactinomas are classified by the size of the tumor as microprolactinoma (< 10 mm), macroprolactinoma (≥ 10 mm), and giant prolactinoma (> 40 mm) [ 13 ]; (2) required treatments included surgery (microscopic surgery or endoscopic surgery) or DAs (bromocriptine or cabergoline). Patients in the DAs group only received DAs, but patients in the surgery group may have received DAs before surgery; (3) included studies reported the data of at least one available outcome that was assessed in this study.…”
Section: Methodsmentioning
confidence: 99%